ACCEPTIBILITY DUBBING PADA FILM ANIMASI ANAK ‘POCOYO’ - Kurniawan, Donie Fadjar (Institut Seni Indoensia Surakarta, 2015)
This study is to explore how the voiceover or dubbing can fulfill all the criteria of a good job in the perspective of Target Language user. To produce voiceover or dubbing in kid film program is really a multi-dimensional job. The first dimension is the linguistic aspects which rules two languages both source language (SL) and target language (TL). Sometimes we find a very long phrase or clause in SLand we finally get the voiceover or dubbing as a quite short phrase or clause and the vice versa. The second dimension is the scope of the social culture that also covers both sides. Sometimes, we find a very difficult terminology in SL to find the acceptability in TL. It is because the specific use relating toevery social and cultural background. English has many words that is hardly found in Indonesia Language. The next dimension is naturality. How a composition in SL should be voiceover or dubbing in the same naturality in the sense of TL. All of those conditions should be answered to the bestsolution by the director of voice over or dubbing. Therefore the results must consider the naturalness language dubbing for children. Vocabulary is selected in such a way that the story can get into the domestic children.The subject of this study is Kid Film Program ‘Pocoyo’ episode A Little Drummer and the Indonesian voice over or dubbing version.Keywords: dubbing, the source language, target language.